UNDERSTANDING ONLINE PURCHASE INTENTION THROUGH ATTRACTIVENESS OF INFLUENCER, BRAND IMAGE, AND PRICE DISCOUNT STRATEGIES - Triyani, Winny Viola; Wibowo, Setyo Ferry; Monoarfa, Terrylina Arvinta (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to examine how attractiveness of social media influencers influence online purchase intention and brand image, brand image influence online purchase intention and price discount influence online purchase intention of Wardah products in Jabodetabek area. This study uses a quantitative method with a purposive sampling technique. Respondents in this study were 200 of female Wardah users in Jabodetabek area. The data analysis technique used structural equation modeling (SEM) with AMOS 24 software. The results demonstrated that: (1) attractiveness of social media influencers had positive and significant influence on online purchase intention, (2) attractiveness of social media influencers had positive and significant influence on brand image, (3) brand image had positive and significant influence on online purchase intention, (4) price discount had positive and significant influence on online purchase intention of Wardah products in Jabodetabek area.